Have drivers at alcohol outlets changed their behavior after the new traffic law? - Raquel B. De Boni; Flavio Pechansky; Mauricio T. de Vasconcellos; Francisco I. Bastos (Brazilian Journal of Psychiatry, 2014)
Objective: In an attempt to reduce high levels of traffic crashes, a new legislation was approved in Brazil in 2008. This study aimed to assess behavioral change among drivers who had drunk at alcohol outlets (AO) after implementation of the law. Method: A three-stage probability sampling survey was conducted in Porto Alegre, state of Rio Grande do Sul, Brazil. Individuals seen leaving AOs after drinking were approached (n=3,018). Selected drivers (n=683) answered a structured interview, were breathalyzed, and had saliva specimens collected for drug screening. Results: Overall, 60.3% (SE 4.5) of drivers reported they did not change their behavior. Among those who reported behavioral changes, most reported drinking less as their main strategy toward safer driving behavior. Variables independently associated with behavior change included having drunk at a high outlet density area (odds ratio [OR] 1.7 [1.1-2.8]) and having a favorable opinion about the law (OR 4.3 [2.1-8.9]). Conclusions: Our findings suggest that awareness of the law has not been enough to promote behavioral change. As most drivers had a favorable opinion of the law and this variable was found to be the strongest predictor of behavior change, efforts to better integrate education and enforcement seem to be pivotal and might be well received by the population.